Estimulación temprana y su impacto en el desarrollo de la psicomotricidad fina en los niños de 4 años de educación inicial de la Unidad Educativa Potosí - Carpio Sánchez, María Fernanda (2023)
The case study demonstrates the importance of psychomotor development through early stimulation activities in four-year-old children, through activities that allow better development in infants. Therefore, it seeks to raise awareness that the infant receives stimulation from the first years of life, in addition to being able to carry out a stimulation program it is necessary to take into account the abilities, skills and needs of the minor. The main purpose of this research work is to improve the development of fine psychomotor skills in 4-year-old children so that they have the necessary knowledge to function in different areas of knowledge, guided by their teacher using different techniques. The research was carried out through the descriptive method, since general aspects that helped to understand the process of early stimulation and its impact on the psychomotor development of the minor were analyzed, therefore, through the surveys carried out, could show that those children who had adequate stimulation do not present major difficulties in the learning process, on the other hand, it was proven that the majority of caregivers, parents and teachers are aware of the benefits and importance of early stimulation and fine psychomotor skills, therefore, they have been cautious when stimulating the main areas of the child's development.